2021
DOI: 10.1038/s41598-021-82275-4
|View full text |Cite|
|
Sign up to set email alerts
|

TDCS effects on pointing task learning in young and old adults

Abstract: Skill increase in motor performance can be defined as explicitly measuring task success but also via more implicit measures of movement kinematics. Even though these measures are often related, there is evidence that they represent distinct concepts of learning. In the present study, the effect of multiple tDCS-sessions on both explicit and implicit measures of learning are investigated in a pointing task in 30 young adults (YA) between 27.07 ± 3.8 years and 30 old adults (OA) between 67.97 years ± 5.3 years. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 106 publications
0
1
0
Order By: Relevance
“…explore basic scientific questions regarding cognitive function (Kaminski et al, 2021). Recent studies have confirmed that this method can up-regulate or down-regulate the excitability of specific brain regions and improve cognitive ability in healthy individuals to perform specific tasks.…”
Section: Introductionmentioning
confidence: 98%
“…explore basic scientific questions regarding cognitive function (Kaminski et al, 2021). Recent studies have confirmed that this method can up-regulate or down-regulate the excitability of specific brain regions and improve cognitive ability in healthy individuals to perform specific tasks.…”
Section: Introductionmentioning
confidence: 98%